Vygotsky's Constructivist Approach in the Use of the Boardgame Codenames in Extracurricular Art Education - Bahastika, Ikrar; Sekti, Retnayu Prasetyanti; Trisakti, Trisakti (Universitas Nusantara PGRI Kediri, 2025)
This study aims to describe the application and effectiveness of Codenames board game media that modified in learning fine arts at the extracurricular